Assessment of Sperm Function Parameters and DNA Fragmentation in Ejaculated Alpaca Sperm (Lama Pacos) by Flow Cytometry - Cheuquemán, C. (2013)
Flow cytometry has been shown to be an accurate and highly reproducible tool for the analysis of sperm function. The main objective of this study was to assess sperm function parameters in ejaculated alpaca sperm by flow cytometry. Semen samples were collected from six alpaca males and processed for flow cytometric analysis of sperm viability and plasma membrane integrity using SYBR-14/PI staining; acrosomal membrane integrity using FITC-conjugated Pisum Sativum Agglutinin/PI labelling; mitochondrial membrane potential (Δψm) by staining with JC-1 and DNA Fragmentation Index (DFI) by TUNEL. The results indicate that the mean value for sperm viability was 57 ± 8 %. Spermatozoa with intact acrosome membrane was 87.9 ± 5%, and viable sperm with intact acrosomal membrane was 46.8 ± 9%, high mitochondrial membrane potential (Δψm) was detected in 66.32 ± 9.51% of spermatozoa and mean DFI value was 0.91 ± 0.9%. The DFI was inversely correlated with high Δψm (p = 0.04; r = -0.41) and with plasma membrane integrity (p = 0.01; r = -0.47). To our knowledge, this is the first report of the assessment on the same sample of several parameters of sperm function in ejaculated alpaca sperm by flow cytometry.